Relationship Between Dietary Patterns and Carotid Atherosclerosis Among People Aged 50 Years or Older: A Population-Based Study in China - Liu, Yunyun; Wang, Xuena; Zhang, Qing; Meng, Ge; Liu, Li; Wu, Hongmei; Gu, Yeqing; Zhang, Shunming; Wang, Yawen; Zhang, Tingjing; Górska, Magdalena J.; Sun, Shaomei; et al. (Frontiers in Nutrition, 2021)
Background: The relationship between dietary patterns and atherosclerosis is inconclusive. Usually, diets vary greatly among different regions due to cultural differences and lifestyles. Few studies to date based on a Chinese population have investigated the relationship between dietary patterns and the formation of atherosclerosis in carotid arteries. We aimed to investigate whether dietary patterns were related to carotid atherosclerosis among an adult population in Tianjin, China. Methods: This cross-sectional study included a total of 2,346 participants aged 50 years or older (mean: 59.7 ± 6.29 years). Dietary intakes were assessed using a validated 81-item semiquantitative food frequency questionnaire, and factor analysis was used to identify dietary patterns. Carotid atherosclerosis was defined as a common carotid artery intima-media thickness ≥1.0 mm or plaques, or a carotid bifurcation intima-media thickness ≥1.2 mm. Multiple logistic regression models were used to explore the relationship between dietary patterns and carotid atherosclerosis. Results: Three factors were determined: “health” dietary pattern (factor 1), “traditional Tianjin” dietary pattern (factor 2), and “sweets” dietary pattern (factor 3). The multivariable-adjusted odds ratios (95% CI) of carotid atherosclerosis for the increasing quartiles of the sweets dietary pattern scores in women were as follows: 1.00 (reference), 1.33 (0.91, 1.97), 1.21 (0.82, 1.79), 1.64 (1.08, 2.51) (p for trend <0.05). No significant difference was found between any dietary pattern and carotid atherosclerosis in men. Conclusion: Greater adherence to “sweets” dietary patterns was positively related to a higher prevalence of carotid atherosclerosis in women aged 50 or older. No relationship was found between any dietary pattern and carotid atherosclerosis in men. Further prospective studies are warranted to test this finding in other populations.